A case report about the detection of infectious hypodermal and hematopoietic necrosis virus (IHHNV) in shrimp displaying no clinical signs or histopathological lesions from farms on Colombia’s north coast - Caicedo, Jahnier A [UNESP]; Vásquez, Gersson M; Calderón, Claudia P; Celis, Eliana [UNESP]; Castro, Jennifer-Natalie; Araujo-Junior, Joao [UNESP]; Mai, Hung N; Dhar, Arun K (Elsevier, 2025)
This study describes the diagnosis and reporting of IHHNV infection in two shrimp farms on Colombia's north coast in 2021. IHHNV was first detected in frozen Penaeus vannamei samples for export. Epidemiological investigation revealed IHHNV prevalence of 97 % and 36 % in the two farms using WOAH-recommended PCR. Histopathology showed no inclusion bodies, but in situ hybridization confirmed infection. Phylogenetic analysis identified the Colombian IHHNV isolates as genotype II, similar to strains from Ecuador, Brazil, and the US. These findings emphasize the importance of integrating molecular diagnostics, genome sequencing, and histopathology with in situ hybridization for comprehensive IHHNV detection and characterization.